The day the crayons made friends - Daywalt, Drew (Philomel, 2025)
Duncan's crayons just can't seem to stay put! After convincing one group of crayons to go back to work after they wanted to quit and rescuing another group who got lost in the most inconvenient places, Duncan's crayons have disappeared once more. But this time they've gone out into his room to make friends. From Red Crayon who fulfills his dream of driving a firetruck, to Blue Crayon, who meets a fashion doll desperately in need of a head, to fan favorite Esteban, who is off to tame a teddy bear (or as he would call it, a wild beast), each crayon has an exciting story to share about the new objects they've met and the new adventures they've had.